A global phylogeny of Pelomedusoides turtles with new material of Neochelys franzeni Schleich, 1993 (Testudines, Podocnemididae) from the middle Eocene, Messel Pit, of Germany (2015)
Background. Neochelys franzeni Schleich, 1993 is the only pleurodire or side-necked turtle from the middle Eocene, Messel Pit (the first UNESCO, World Natural Heritage Site in Germany, since 1995). The original description of the species is based on two specimens SMF ME 1091 (Holotype) and 715 (Paratype) housed at the Senckenberg Museum Frankfurt. The excellent preservation of complete and articulated skeletons of this species makes it a key taxon for understanding the evolution and phylogeny of the European Neochelys genus and its relationships with South American and African-Madagascar podocnemidids. Results. Five new specimens of Neochelys franzeni fromMessel Pit are described here, together with the redescription of SMF ME 1091 and 715. Specimens correspond to individuals of different ontogenetic stages showing conservative morphology from hatching to adults. A revised diagnosis for the species is presented here, together with its inclusion in a global phylogenetic analysis of Pelomedusoides that shows that this species and the whole Neochelys spp. is sister to the Erymnochelys madagascariensis-Peltocephalus dumerilianus clade within Podocnemididae